PEWARISAN SEJARAH MELALUI ADAT MANGONGKAL HOLI BATAK TOBA DI DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN SUMATERA UTARA TAHUN 2019 - Mariana, Dina (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2021)
In a cultural heritage that exists in the life of the Batak Toba people, there must be a history of how the custom existed. such as the history of the Mangongkal Holi custom that exists in the Toba Batak community, precisely in the Humbang Hasundutan Regency, Doloksanggul District which is still being implemented and preserved to this day. The implementation of this Mangongkal Holi custom is because there are several driving factors that can be seen in the life of the Batak community itself. So that with the emergence of a history of the Toba Batak culture, it has led to the implementation or procedures in this custom where the implementation forms a historical inheritance containing values ​​that are very important to be known by the Toba Batak community itself, especially the youth, where the youth must be able to know how is the history of a Mangongkal Holi custom because youth are the next generation of traditional implementers in a community, especially the Batak community